2021
DOI: 10.1016/j.toxrep.2021.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin-rich fraction from Sargassum fusiformis alleviates particulate matter-induced inflammation in vitro and in vivo

Abstract: Particulate matter (PM) contributes to air pollution and primarily originates from unregulated industrial emissions and seasonal natural dust emissions. Fucoxanthin (Fx) is a marine natural pigment from brown macroalgae that has been shown to have various beneficial effects on health. However, the effects of Fx on PM-induced toxicities in cells and animals have not been assessed. In this study, we investigated the anti-inflammatory potential of the Fx-rich fraction (FxRF) of Sargassum fusiformis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Similar inflammatory gene expression was observed in UVA-induced reconstructed human skin [ 39 ]. In cultured human keratinocytes, fucoxanthin reduced COX-2, PGE2, ILO-6, IL-1β, and TNF-α, iNOS, and PGE2 levels in particulate matter (PM)-induced macrophages [ 40 ]. Moreover, in PM-induced zebrafish embryos, fucoxanthin attenuated NO and ROS levels and thereby inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar inflammatory gene expression was observed in UVA-induced reconstructed human skin [ 39 ]. In cultured human keratinocytes, fucoxanthin reduced COX-2, PGE2, ILO-6, IL-1β, and TNF-α, iNOS, and PGE2 levels in particulate matter (PM)-induced macrophages [ 40 ]. Moreover, in PM-induced zebrafish embryos, fucoxanthin attenuated NO and ROS levels and thereby inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Since seaweeds have low Fx contents (0.02–0.58% fresh weight), obtaining sufficient quantities of Fx for commercial applications is a significant challenge [ 91 ]. However, FxRF extracts, which contain Fx and other similar bioactive pigments, are easily obtained [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fucoxanthin, a bioactive compound in seaweed, decreased cell viability by 60% and cytokine levels in macrophages and keratinocytes by inhibiting the MAPK pathway, indicating its therapeutic effect during inflammation. Moreover, in particulate matter (PM)-exposed zebrafish embryos, fucoxanthin significantly reduced the expression levels of factors involved in inflammatory responses and cell death, including NO and reactive oxygen species [ 8 ]. Previous reports have shown that H. fusiformis extract decreases iNOS expression and NF-κB translocation, and increases the activation of MAPKs and STAT1 phosphorylation [ 114 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, zebrafish ( Danio rerio ), which have great advantages as an in vivo animal model, is widely used as a powerful vertebrate animal model for the study of human diseases [ 53 54 ]. In particular, since PM-stimulated zebrafish exhibit inflammatory and oxidative reactions similar to those of mammals, and is recognized as an optimal in vivo model for evaluating anti-inflammatory and antioxidant efficacy of various drugs [ 55 56 57 58 59 ]. Since in vivo experiments can provide a better understanding of efficacy assessment at the organism level, the anti-inflammatory and antioxidant potential of SF identified in macrophages was further confirmed in the zebrafish model.…”
Section: Discussionmentioning
confidence: 99%